2014
DOI: 10.3126/jcmc.v3i4.9547
|View full text |Cite
|
Sign up to set email alerts
|

Profile Of Neonatal Admission At Chitwan Medical College

Abstract: In Nepal, three most common causes of newborn (NB) admission in the neonatal intensive care unit (NICU) are birth asphyxia, neonatal sepsis and prematurity and they are the leading causes of death too. A study previously done in Nepal shows asphyxia as a leading cause of hospital admission accounting 22% followed by prematurity 20% and neonatal sepsis 17% with mortality due to these three causes being 7%, 3% and 5% respectively. Reasons of NICU admission in Chitwan Medical College (CMC) are clinical sepsis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 4 publications
6
9
0
Order By: Relevance
“…In a study done by Shakya A et al in KIST Medical College, Lalitpur, there was a male predominance with a male to female ratio of 1.4:1. 12 Similar pattern of male dominance was found in a study conducted by Shrestha SP et al in Chitwan Medical College and Teaching Hospital where they found male to female ration of 1.8:1. 13 Kanodia P et al also found male predominance in a study conducted in BP Koirala Institute of Health Sciences, Dharan, Nepal.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In a study done by Shakya A et al in KIST Medical College, Lalitpur, there was a male predominance with a male to female ratio of 1.4:1. 12 Similar pattern of male dominance was found in a study conducted by Shrestha SP et al in Chitwan Medical College and Teaching Hospital where they found male to female ration of 1.8:1. 13 Kanodia P et al also found male predominance in a study conducted in BP Koirala Institute of Health Sciences, Dharan, Nepal.…”
Section: Discussionsupporting
confidence: 78%
“…Similar finding was found in a study conducted by Shakya A et al where 89.2% were term and 10.8% preterm. 12 This finding was different from other centers where the percentages of premature babies were higher (23.8% to above 50%). [15][16][17] This is probably due to the fact that our hospital has only special baby care unit with no mechanical ventilators and so preterm babies are referred to higher center for further evaluation.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Previous studies from Nepal have reported incidence from 3.9% to 8.0%. 6 However, these studies have just been limited to an overview of the NICU admissions and the causes of the respiratory distress has not been discussed. In our study, we found the common causes of respiratory distress in neonates were MAS in 21.1% followed by septicemia in 16.5% out of which 33.3% were culture proven sepsis, TTN in 15.5%, pneumonia in 14.6%, birth asphyxia in 11.9%, hyaline membrane disease in 11.9%, and congenital heart disease in 6.4%.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of respiratory distress varies with gestational age: 30.0% among preterm, 20.0% among post terms to 4.0% in term babies. Assuming prevalence of respiratory distress as 7.5% [6][7][8] and level of significance of 5.0 %, sample size was calculated using formula N= z 2 pq/d 2 where, p= prevalence of respiratory distress in newborns. q = 1-p, N= sample size, z=1.96, d= maximum tolerable error.…”
mentioning
confidence: 99%